2021
DOI: 10.1007/s12134-021-00906-1
|View full text |Cite
|
Sign up to set email alerts
|

A Black-Box yet To Be Opened: Multi-level Processes During Migrants’ Organizational Socialization

Abstract: Migrants entering a new country also search for belonging. Through employment, migrants work in organizations and experience socialization in these new contexts. Thereby, organizations offer migrants a wide range of possibilities for identification and are thus places to regain a sense of belonging. We rely on prior research showing what migrants experience during the process of organizational socialization to organizational identification, more specifically through (a) sense-making which (b) provides self-est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 85 publications
0
2
0
Order By: Relevance
“…Studying integration is crucial for cross-cultural management and migration research because the processes and outcomes of mobility-related interactions and experiences are key concerns for both fields. Cross-cultural management research recognises that migrants can add value to organizations through their alternative perspectives and problem-solving strategies, which can be accessed and used strategically when migrants are integrated effectively into the workforce (Fitzsimmons et al, 2011; Grosskopf et al, 2022; Hajro et al, 2017; Hong and Minbaeva, 2022). However, cross-cultural management and migration research has shown that the inclusion of migrants in specific workplaces, and labour markets more widely, requires us to understand the factors that shape practices and experiences of integration (Fang et al, 2013; Hajro et al, 2021; Janta et al, 2012; Lugosi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Studying integration is crucial for cross-cultural management and migration research because the processes and outcomes of mobility-related interactions and experiences are key concerns for both fields. Cross-cultural management research recognises that migrants can add value to organizations through their alternative perspectives and problem-solving strategies, which can be accessed and used strategically when migrants are integrated effectively into the workforce (Fitzsimmons et al, 2011; Grosskopf et al, 2022; Hajro et al, 2017; Hong and Minbaeva, 2022). However, cross-cultural management and migration research has shown that the inclusion of migrants in specific workplaces, and labour markets more widely, requires us to understand the factors that shape practices and experiences of integration (Fang et al, 2013; Hajro et al, 2021; Janta et al, 2012; Lugosi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A disparate range of organisations and their constituent actors influence migrants' transition into and through the labour market (Calò et al, 2021;Grosskopf et al, 2021;Siviş, 2021). Various informal networks, formal organisations and institutions including charities, branches of faith-based bodies, social enterprises and non-governmental organisations (NGOs) help to develop migrants' general employability and facilitate their access to work (Aerne & Bonoli, 2021;Bagavos & Kourachanis, 2021;İçduygu & Diker, 2017;Siviş, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Organizational socialization is the process by which organizational newcomers 1 acquire the necessary knowledge and skills to adjust to an organizational role or a new job (Van Maanen & Schein, 1979;Allen et al, 2017). Recent studies (e.g., Grosskopf et al, 2022;Omanović & Langley, 2023;Tharenou & Kulik, 2020) demonstrate the relevance of adopting theoretical constructs developed from organizational socialization to understand the challenges facing immigrants when socializing into receiving-country organizations. They also identify specific organizational practices that can be of great use in facilitating the socialization process.…”
Section: Immigrant Socializationmentioning
confidence: 99%
“…Colleagues in the organizations are important socialization agents for migrants new to the receiving country. For instance, Grosskopf et al (2022) found that migrants' colleagues in the German workplace not only socialized them into organizational insiders but also increased migrants' identification with professional cultures and the broader society.…”
Section: Immigrant Socializationmentioning
confidence: 99%
See 1 more Smart Citation